Specific features of physical development in children and adolescents with type 1 diabetes mellitus - Viktoriya Nikolaevna Panfilova; Tatiana Evgen'evna Taranushenko; Oksana Alexeevna Terent'eva; Maria Nikolaevna Petrova (Сахарный диабет)
Aim. To evaluate variations of principal parameters of physical development in children and adolescents with type 1 diabetes. Materials and methods. The study included 356 children with DM1. Their height, body weight, and body mass index were compared with the respective valuesfrom percentile tables recommended by WHO and US Centre for Disease Control and Prevention. For each patient, height deviation from the mean valuewas expressed as SDS. For the assessment of physical development, the place of each parameter in one of the 7 centile intervals was determined. Harmonicityof physical development was estimated from the difference between normal intervals on the centile scale after measurement of height and body weight.Results.Most patients (55,7%) were found to harmonically develop during the 9 year-long study, 30% had excess body weight despite average height. DM1was associated with reduced SDS values for the height and parallel increase of body weight especially in the disease over 10 years in duration. The HbA1c levelin low-height patients was significantly elevated compared with high-height ones. Negative effect of long-term metabolic decompensation on the growth of thechildren became apparent since the third year of the disease. Body weight was a more stable parameter independent of the degree of compensation.Conclusion: Children and adolescents with DM1 experience deterioration of yearly height dynamics with increasing length of the disease. Growth characteristicsare related to the degree of compensation of carbohydrate metabolism.